Evaluation of the behavior of the sea level of the Malaysian waters during EL Nino and LA Nina events - Hashim, Noor Baharim; Shamsudin, Supiah; Alejandro, Livio Camerlengo; Abd. Malek, Anie Raflikha (Faculty of Civil Engineering, 2007)
The northeast monsoon from South China Sea is the major rainy season in the country. Heavy rain that occurs in the end of the year often cause severe flood along the east states of Kelantan, Terengganu, Pahang and East Johor in Peninsular Malaysia and in Sarawak in East Malaysia. Purpose of this study is to determine the variation of Malaysian sea level during El Nino and La Nina event, specifically during the northeast and southwest monsoon that occur from late November to Mac and from June to September every year respectively. The southwest monsoons is drier compared to northeast monsoons with minimum rainfall. From this study, the sea level increases during the northeast monsoon compared to the southwest monsoon. ENSO event also affected the sea level during these monsoons season.